2017
DOI: 10.1227/neu.0000000000001374
|View full text |Cite|
|
Sign up to set email alerts
|

Defining Glioblastoma Resectability Through the Wisdom of the Crowd: A Proof-of-Principle Study

Abstract: In this pilot study, we demonstrate the feasibility of measuring the resectability of glioblastoma through crowdsourcing. This tool could be used to quantify resectability, a potential confounder in neuro-oncology clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Indeed, results of surveys on surgeons’ surgical plans correlates much more strongly with extent of resection than known predictive variables and clinical scales [47], suggesting that the decision-making process is incompletely captured with standard analyses such as ours. Moreover, Orringer et al found 28.3% disagreement between academic tumor surgeons about the feasibility of gross total resection for given lesions, suggesting that further highlighting the complexity of the decision and its inability to be reduced to simple binary variables [48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results of surveys on surgeons’ surgical plans correlates much more strongly with extent of resection than known predictive variables and clinical scales [47], suggesting that the decision-making process is incompletely captured with standard analyses such as ours. Moreover, Orringer et al found 28.3% disagreement between academic tumor surgeons about the feasibility of gross total resection for given lesions, suggesting that further highlighting the complexity of the decision and its inability to be reduced to simple binary variables [48].…”
Section: Discussionmentioning
confidence: 99%
“…which may serve as confounders when comparing the PCNSL cohort to the non-PCNSL cohort. Finally, as is the case with all brain tumors, determining the resectability of the tumor in PCNSL is a crucial step in the decision making process and should be part of the consideration when deciding between craniotomy versus biopsy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this information is included in the web card, and is indexed by the Lucene/Solr search engine. Therefore, searching MalaCards provides users with direct access to dozens of disease information sources in one go, akin to crowd wisdom (29). The MalaCards search provides a default set of section weights.…”
Section: Search and Navigationmentioning
confidence: 99%